Beauty and monstrosity in art and culture - Kokkiou, Chara, 1964-; Malakasioti, Angeliki (Abingdon, Oxon : Routledge, 2024)
"This edited volume takes a new look at an old question: what is the relationship between beauty and monstrosity? How has the notion of beauty transformed through the years and how does it coincide with monstrous ontologies? Contributors offer an interdisciplinary approach to how these two concepts are interlinked and emphasizes the ways the beautiful and the monstrous pervade human experience. The two notions are explored through the axis of human transformation, focusing on body, identity and gender, while questioning both how humans transform their body and space as well as how humans themselves are gradually transformed in different contexts. The pandemic, gender crisis, moral crisis, sociocultural instability, and environmental issues have redefined beauty and the relationship we have with it. Exploring these concepts through the lens of human transformation can yield valuable insights into what it means to be human in a world of constant change. The book will be of interest to scholars working in art history, archaeology, philosophy, architecture, and cultural studies"--
Infernal women : polysemic winged figures in Etruscan art / Bice Peruzzi -- Beauties and beasts : a personal lens to the backstage of story-creation / Alexandra Antonopoulou -- Truth, beauty, and hungry monsters / Chris Hables Gray.
Keywords: Human body (Philosophy); Human beings in art; Aesthetics; Monstrosity; ART / Popular Culture; HISTORY / Ancient / General